PENGARUH RENDAHNYA KINERJA KARYAWAN PADA CV ABCD - Ageng Saepudin Kanda; Moch Adi Firmansyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract Quality employee performance provides progress in achieving a desire for the company, if they have achieved high performance they will achieve and show success, workers are also required to be responsible and able to complete the work that has been set by the company. Therefore, in order to achieve the company's desired goals, excellent performance is required. The author researches companies using qualitative methods. The opinion expressed by Anslem Strauss, research using qualitative methods is a type of research whose findings do not involve statistical procedures or calculations. With qualitative methods, searching for deeper information can maximize employee performance. There are several points that influence the low performance of workers, namely a low level of education which is very influential because a lack of education level will also result in a lack of knowledge about work. If only the level of education is adequate then the company can have quality employees and this can be profitable for the company. If there is no supervision in a company, the low performance of employees will not be able to be evaluated because the superiors do not know about the employees during operational hours. From the statement above, it is necessary to take these factors into account so that we can evaluate the company better and achieve a goal or success. Keywords: Knowledge, Performance, Employees, Education, Quality.